The existence and uniqueness of the solutions for a system of some fractional order nonlinear differential equations - Raad Putrus; Hamsa Saleem (College of Education for Pure Sciences, 2008)
ABSTRACT In this paper, we study an existence and uniqueness of the solutions for some nonlinear differential equations which has fractional order , in the case , by using the picard approximation method .and through this study we obtained on many computation in the solutions of the existence and uniqueness theorems for the same fractional nonlinear differential equations. Further more this study development and extended the previous method , such that the solutions and computations which has been obtained became more general and universal.